U-shaped relationship between serum uric acid and gastric cancer risk: a large prospective cohort study - Junjun Huang; Ningning Mi; Jingli Yang; Ya Zheng; Jinqiu Yuan; Jinqiu Yuan; Wenbo Meng; Wenbo Meng; Wenbo Meng; Wenbo Meng; Wenbo Meng (Frontiers in Oncology)
ObjectiveWe conducted this study to investigate the relationship between serum uric acid (SUA) levels and the risk of upper gastrointestinal cancer.MethodsWe conducted a prospective cohort study with 475659 cancer-free participants from the UK Biobank. All subjects were grouped into quartiles, and we used a Cox proportional hazards model to analyze the association between SUA levels and the risk of upper gastrointestinal cancer and explore the potential sex-specific relationship.ResultsOf the 475659 participants, 883 eventually developed upper gastrointestinal cancers over a median follow-up period of 6.7 years. We observed that SUA level was positively correlated with the risk of female oral cancer (hazard ratio Quartile 4 vs Quartile 1 (95% CI): 2.05(1.03,4.06)) and negatively associated with the risk of esophageal cancer in the general population (hazard ratio Quartile 3 vs Quartile 1 (95% CI): 0.65(0.45,0.93)). The risk of gastric cancer in males showed a U-shaped trend, decreasing and then increasing as SUA levels increased (hazard ratio Quartile 3 vs Quartile 1 (95% CI): 0.51(0.32,0.81)). The risk of small intestine cancer in females showed a trend of increasing and then decreasing with increasing SUA levels (hazard ratio Quartile 3 vs Quartile 1 (95% CI): 3.34(1.10,10.13)). Interaction analysis indicated that various factors, such as age, sex, smoking and drinking status, family history of cancer and BMI might play an important role in the relationship between SUA and cancer.ConclusionSUA levels are positively associated with the risk of oral cancer risk in females and negatively associated with the risk of esophageal cancer in the general population. Both low and high SUA levels were associated with increased risk of gastric cancer, supporting a U-shaped association.